An evaluation of the coursebook “English for Pharmaceutical course” for the second - year students at Văn Hiến medical and pharmaceutical school. - Nguyễn, Thị Thảo (University of Languages and International Studies, 2017)
Material evaluation plays an integral part of English language teaching and learning. This study is carried out to evaluate the material “English for pharmaceutical course” which is currently used for the second year pharmaceutical students at Van Hien Int (...)